Low-molecular-mass aspartic protease inhibitor from a novel penicillium sp.: implications in combating fungal infections - Menon, Vishnu; Rao, Mala (Microbiology-SGM, 2012)
A low-molecular-mass aspartic protease inhibitor was isolated from a novel Penicillium sp. The inhibitor was purified to homogeneity, as shown by reversed-phase HPLC and SDS-PAGE. The M-r of the inhibitor was 1585 and the amino acid composition showed the presence of D, D, D, E, A, K, L, Y, H, I and W residues. The steady-state kinetic interactions of Aspergillus saitoi aspartic protease with the inhibitor revealed the reversible, competitive, time-dependent tight-binding nature of the inhibitor, with IC50 and K-i values of 1.8 and 0.85 mu M, respectively. Fluorescence spectroscopy and circular dichroism analysis showed that inactivation of the enzyme was due to binding of the inhibitor to the active site. The inhibitor was found to inhibit mycelial growth and spore germination of Aspergillus fumigatus and Aspergillus niger in vitro with MIC values of 1.65 and 0.30 mu g ml(-1), respectively. This study will potentially open the way towards the development of a tight-binding peptidic inhibitor against fungal aspartic proteases to combat human fungal infections.